Production of Cold-Active Lipase by Free and Immobilized Marine Bacillus cereus HSS: Application in Wastewater Treatment - Hassan, Sahar W. M.; Abd El Latif, Hala H.; Ali, Safaa M. (Frontiers in Microbiology, 2018)
Lipases are enzymes have potential for hydrolysis of triacylglycerol to free fatty acids and glycerol and are used in dissimilar applications. The aim of the present study was isolation, screening of marine bacteria for lipase production, optimization of production and wastewater treatment. Twenty marine bacterial isolates were isolated from Mediterranean sea and screened for lipase production. All isolates were found to have lipolytic ability. The differences between isolates were studied using RAPD-PCR. The most promising lipase producer (Isolate 3) exhibited the highest lipolytic hydrolysis (20 mm) was identified as Bacillus cereus HSS using 16S rDNA analysis. Optimization of lipase production was carried out using Plackett Burman experimental design using cotton seed oil as inducer under shake conditions at 10 oC. The most significant factors affected lipase production were FeSO4, KCl and oil concentrations. Lipase activity increased by 1.8 fold compared to basal conditions by using the optimized culture conditions. Immobilization by adsorption of cells on sponge raised lipase activity compared to free cells. Repeat reuse of the immobilized B. cereus HSS maintained reasonable lipase activity. A trial for economic treatment of oily wastewater was carried out. Removal efficiency of biological oxygen demand, total suspended solids and oil &grease was 87.63%, 90% and 94.7%, respectively which is a promising for future applications.